2014
DOI: 10.1523/jneurosci.1526-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modification of the Glucocorticoid Receptor Gene Is Linked to Traumatic Memory and Post-Traumatic Stress Disorder Risk in Genocide Survivors

Abstract: Recent evidence suggests that altered expression and epigenetic modification of the glucocorticoid receptor gene (NR3C1) are related to the risk of post-traumatic stress disorder (PTSD). The underlying mechanisms, however, remain unknown. Because glucocorticoid receptor signaling is known to regulate emotional memory processes, particularly in men, epigenetic modifications of NR3C1 might affect the strength of traumatic memories. Here, we found that increased DNA methylation at the NGFI-A (nerve growth factor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(124 citation statements)
references
References 61 publications
2
115
0
Order By: Relevance
“…Specifically, the site is 2803 bp downstream from the first CpG site analyzed by Oberlander et al [2] in the 1F promoter, the region of NR3C1 that has been most frequently studied in methylation analyses [5,10,[38][39][40][41][42][43][44][45][46][47]. We …”
Section: Rationale For Cpg Site Chosenmentioning
confidence: 99%
“…Specifically, the site is 2803 bp downstream from the first CpG site analyzed by Oberlander et al [2] in the 1F promoter, the region of NR3C1 that has been most frequently studied in methylation analyses [5,10,[38][39][40][41][42][43][44][45][46][47]. We …”
Section: Rationale For Cpg Site Chosenmentioning
confidence: 99%
“…5 The structure of NR3C1 is highly conserved between human, rat, 6 and mouse 7 ; strong homologies are also found in multiple 5'untranslated exons in the proximal promoter regions, which produce various mRNA isoforms encoding the same protein. 8 Pioneer studies in the rat showed that persistent changes in exon 1 7 DNA methylation occur as a function of quality of maternal care 9 ; subsequently, childhood trauma, suicide, 15,16 BPD, [17][18][19] and PTSD [20][21][22] were shown to produce similar epigenetic modifications. While most of the latter studies focused on exon 1F, the human homolog of 1 7 , some authors reported upregulation of multiple transcripts after early-life stress (ELS).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in both humans and animals have suggested that the epigenetic regulation of distinct genes play roles in the pathogenesis of PTSD (Labonté et al, 2014;Byun et al, 2015). Vukojevic et al (2014) reported that an epigenetic alteration in the glucocorticoid receptor (GR) gene promoter is linked to individual and gender-specific differences in memory function and risk of PTSD. Additionally, evidence of this epigenetic regulation has been found in an animal model of fear conditioning (Kwapis and Wood, 2014).…”
Section: Introductionmentioning
confidence: 99%